Assessing the Effectiveness of Contextual Based Learning Videos in Waves - Putri Bullquis Marsa; Desnita Desnita (Jurnal Pembelajaran Fisika, 2020)
This study aims to produce a valid instrument in assessing the effectiveness of contextual video-based wave material as an instructional medium of physics. The instrument consists of four sets; namely critical thinking skills instruments, creative thinking skills instruments, collaboration skills instruments, and communication skills instruments both oral and written. This research uses the type of development research. The development procedure consists of 10 stages. The instrument was validated by 2 experts. The validity category refers to the opinion of Aiken's V, where the value ≥ 0.6 of the instrument is considered valid. To assess instrument validity the instrument validation assessment sheet was used. Based on the results of the instrument validation assessment conducted by the experts, it was found that all the instruments were considered valid with the average value of the critical thinking skills instrument of 0,91, instruments of 0,93, collaboration skills instruments of 0,99, oral communication skills instruments of 0,98, and written communication skills instruments of 0,90. Thus all instruments can be used to validate the learning video that will be developed.Keywords: assessment, an instrument of effectiveness, contextual, waveDOI: http://dx.doi.org/10.23960/jpf.v8.n1.202010